THE HUMAN CAPITAL MANAGEMENT PRACTICES A HIGHER EDUCATION: MAPPING AND MEASURING THE MATURITY LEVEL - Emilia Fitriana Dewi; Dematria Pringgabayu; Hendriady de Keizer (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
In order to improve human capital capacity, this research aimed at mapping the maturity level and the role of human capital management (HCM) in the institution. The research employed qualitative and quantitative approach (mixed methods) among 58 respondents, including lecturers and academic staff. FGD and the questionnaires were administered after a comprehensive briefing about HCM principles using Bassi and McMurrer as well as Ulrich frameworks. Results indicated low scores (2.92 = poor) in all five human capital drivers which reflexed low HCM maturity level in the institution. Moreover, perception of the participants about the role of HCM in the institution was also poor since the score was only achieving 60.8% which was still below the standard of 80%. These results suggest the importance of systematic steps in order to develop HCM in the institution